Effects of Solar Shading on Thermal Comfort in Low-income Tropical Housing. (March 2017) - Hashemi, Arman; Khatami, Narguess
Abstract: This paper evaluates the effects of solar shading strategies on thermal comfort in low-income tropical housing in Uganda. Dynamic thermal simulations are conductedand the effects of various shading strategies including curtains, roof and window overhangs, veranda and tress on solar heat gain and thermal comfort are investigated.Adaptive approach for naturally ventilated buildings defined by CEN standardis used to assess theconditions in the case study buildings. According to the results, although shading significantly reduces solar heat gain, it is less effective inmeeting thermal comfort requirements in low-income tropical houses. Solar shading is however considerably effective during the hottest periods of the year reducing the risk of extreme overheating by up to 52%.In this respect, a north-south building orientation with the main openings on the north elevation is recommended. Due to excessive solar heat gain, large openings on east- and west-facing walls should be avoided.